Overcoming barriers in developing digital skills for higher education teachers: challenges and solutions - Knyazeva, Nina; Mikhailova , Irina; Usmanova, Natalya; Shindina, Tatyana (Review of Artificial Intelligence in Education, 2022)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="815b3dda-3583-4767-a775-fab11fa4d30d"> Objective: Investigate barriers to higher education teachers' development of digital competencies and propose solutions. Method: A survey was conducted among teachers at the National Research University "MPEI" to classify barriers into organizational, technical, methodological, and psychological categories. Results: The survey identified significant organizational and psychological barriers. Proposed solutions include assessing teachers' digital competencies and incorporating these assessments into performance indicators, alongside comprehensive support systems for teachers. Practical Implications: Emphasizes the need for collaborative efforts between university administration and teachers to enhance digital competencies, crucial for adapting to digital education. Conclusions: Developing digital competencies among higher education teachers is vital for successful digital education adaptation, requiring joint efforts to overcome identified barriers and improve educational quality.